Secondary Hydrogeologic Regions of the Conterminous United States. Issue 3 (9th August 2018) - Belitz, Kenneth; Watson, Elise; Johnson, Tyler D.; Sharpe, Jennifer
Abstract: The U.S. Geological Survey (USGS) previously identified and mapped 62 Principal Aquifers (PAs) in the U.S., with 57 located in the conterminous states. Areas outside of PAs, which account for about 40% of the conterminous U.S., were collectively identified as "other rocks." This paper, for the first time, subdivides this large area into internally‐consistent features, defined here as Secondary Hydrogeologic Regions (SHRs). SHRs are areas of other rock within which the rocks or deposits are of comparable age, lithology, geologic or physiographic setting, and relationship to the presence or absence of underling PAs or overlying glacial deposits. A total of 69 SHRs were identified. The number and size of SHRs identified in this paper are comparable to the number and size of PAs previously identified by the USGS. From a two‐dimensional perspective, SHRs are complementary to PAs, mapped only where the PAs were not identified on the USGS PA map and not mapped where the PAs were identified. SHRs generally consist of low permeability rocks or deposits, but can include locally productive aquifers. The two maps, taken together, provide a comprehensive, national‐scale hydrogeologic framework for assessing and understanding groundwater systems. Abstract : Article impact statement : Identification of Secondary Hydrogeologic Regions in areas outside of Principal Aquifers expands the framework for U.S. national assessments.